The Creative Process Perspectives from Multiple Domains (Palgrave Studies in Creativity and Culture, 2018)
The creative process refers to the sequence of thoughts and actions that are involved in the production of new work that is both original and valuable in its context. This book examines this process across the domains of visual art, writing, engineering, design and music. It characterizes each domain's creative process based on evidence stemming from creators' accounts of their own activity and a wide-range of observational material and theories specific to each field. Results from empirical research are then presented across a set of closely linked chapters, using a common set of methodologies that seek to trace the creative process as it unfolds. This highly interdisciplinary edited collection offers valuable insight into the creative process for scholars and practitioners in the fields of psychology, education, and creative studies, as well as for any other readers interested in the creative process. Todd Lubart brings together a group of authors who are themselves actively involved in their respective creative fields and invites readers to adopt a broad perspective on the creative process in order to unravel some of its mysteries. .